Application of Oxytocin Massage as an Effort to Create a Healthy and Happy Postpartum - Ika Fitria Ayuningtyas; Lutfi Hidiyaningtyas; Dwi Kartika Rukmi (Universitas Jenderal Achmad Yani Yogyakarta, 2025)
Awareness of the importance of exclusive breastfeeding has increased among parents. However, several challenges remain, one of which is the inability of mothers to breastfeed until their babies are six months old. This is often attributed to mothers' lack of understanding of proper breastfeeding techniques, including methods to support optimal breast milk production. The purpose of the community service program is to increase breast milk production through oxytocin massage. The method used is divided into three stages: a pretest, providing material on oxytocin massage, followed by an oxytocin massage demonstration, and finally a posttest. The results obtained were 36 respondents, 100% of whom had good knowledge. The posttest results showed a 16.66% increase in knowledge scores compared to the pretest. Husbands/family members were willing to simulate oxytocin massage after being given a demonstration by the midwife. The community service program hopes that husbands/family members will continue to provide oxytocin massage at home for 2-3 minutes every day